Virtual reality rehabilitation program on executive functions of children with specific learning disorders: a pilot study - Di Giusto, Valentina; Purpura, Giulia; Zorzi, Carla Fulvia; Blonda, Rosanna; Brazzoli, Elena; Meriggi, Paolo; Reina, Tarjn; Rezzonico, Silvia; Sala, Roberta; Olivieri, Ivana; Cavallini, Anna (Frontiers in Psychology, 2023)
Background The application of Virtual Reality (VR) in the field of rehabilitation has been widely studied, because it has already proven to be an effective intervention for a variety of physical and cognitive conditions. Nevertheless, its application in pediatric rehabilitation is more recent. This pilot study aims to examine whether a VR-rehabilitation program may have positive effects on the Executive Functions (EFs) of children with Specific Learning Disorders (SLD). Materials and methods Twenty-four children with diagnosis of SLD participated to the study (range 7–11 years) and performed the VR-training across 6 weeks in the CARE Lab, that was designed with appropriate structural measures and ad hoc fittings, to hide the sophisticated technology necessary to allow the child to experience a rehabilitative setting with recreational and semi-immersive features. Children were evaluated across three main time-points: T0, assessment of cognitive level and EFs immediately before the start of the intervention; T1, assessment of EFs immediately after the end of VR intervention; T2, follow-up of EFs after 6 months from the end of the VR intervention. The rehabilitation programs were customized according to clinical needs and/or single patient’s characteristics, proposing different games with variable complexity levels. Results Results showed that scores for visual attention, inhibition, flexibility, and planning abilities were significantly higher than before the intervention, and the most part of these ameliorations were maintained after 6 months. Conclusion These findings provide important inputs for the development of new innovative rehabilitation interventions for children with SLD that must be founded in ecological and evidence-based approaches.